The MANAJEMEN SARANA DAN PRASARANA DALAM MENINGKATKAN MUTU PENDIDIKAN DI SEKOLAH MENENGAH ATAS ISLAM TERPADU NURUL ILMI JAMBI - L, Samsu Alam; Samsu, Samsu; MY, Mahmud (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
The quality of education is influenced not only by the competence of educators but also by the availability and effective management of adequate facilities and infrastructure. This study aims to examine the management of facilities and infrastructure in improving the quality of education at Nurul Ilmi Integrated Islamic Junior High School, Jambi City. Using a qualitative descriptive method, data were collected through interviews, observations, and documentation, then analyzed through data reduction, presentation, and conclusion drawing. The findings reveal that facilities and infrastructure management is carried out optimally through systematic planning, stakeholder involvement, alignment with school needs, and compliance with regulations such as the Ministry of Education’s guidelines and BOS funding provisions. Procurement is conducted in stages based on real needs and coordinated with the relevant teams to ensure efficiency and accountability. Available facilities including comfortable classrooms, laboratories, a digital library, a school mosque, and sports areas significantly contribute to effective learning and the formation of students’ Islamic character. This study concludes that well-planned and coordinated facilities management serves as a key strategy to enhance educational quality in integrated Islamic schools.